Fgf signalling triggers an intrinsic mesodermal timer that determines the duration of limb patterning - Sofia Sedas Perez; Caitlin McQueen; Holly Stainton; Joseph Pickering; Kavitha Chinnaiya; Patricia Saiz-Lopez; Marysia Placzek; Maria A. Ros; Matthew Towers (Nature Communications, 2023)
Abstract Complex signalling between the apical ectodermal ridge (AER - a thickening of the distal epithelium) and the mesoderm controls limb patterning along the proximo-distal axis (humerus to digits). However, the essential in vivo requirement for AER-Fgf signalling makes it difficult to understand the exact roles that it fulfils. To overcome this barrier, we developed an amenable ex vivo chick wing tissue explant system that faithfully replicates in vivo parameters. Using inhibition experiments and RNA-sequencing, we identify a transient role for Fgfs in triggering the distal patterning phase. Fgfs are then dispensable for the maintenance of an intrinsic mesodermal transcriptome, which controls proliferation/differentiation timing and the duration of patterning. We also uncover additional roles for Fgf signalling in maintaining AER-related gene expression and in suppressing myogenesis. We describe a simple logic for limb patterning duration, which is potentially applicable to other systems, including the main body axis.